NILAI-NILAI EKOLOGI DALAM “PEGASUS JATUH” DAN PENGGUNAANNYA DALAM PEMBELAJARAN SASTRA - Titik Dwi Ramthi Hakim; Nifa Kurnia Fahmi; Wakhidatul Ilmia (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
Ecological Values in “Pegasus Jatuh” and The Use It In Teaching Literature. The purpose of this study, first, is to analyze the echocritical element reflected by the author through the short story Pegasus Jatuh. Second, integrate ecological values in literature teaching. This study used descriptive qualitative method. The approach used is Garrard's eco-criticism. Sources of data obtained from the behavior of characters in the short story. Data analysis begins by marking words, phrases, clauses, and sentences that have a focus on environmental exploitation. The results show in the short story “Pegasus Jatuh”, the author reflects environmental phenomena that include illegal logging, buying and selling protected animals, and exploitation of gold. The analysis applied in literature learning which has an important role in character education. Literature in education has a role to develop the language, cognitive, affective, psychomotoric, personality, and social aspects of students.